Effect of Granule and Liquid Biofertilizers on Growth and Yield of Maize Under Several Levels of Drought Stress - Fitroni, Achmad Syakur; Iriany, Aniek; Ishartati, Erny (Journal of Tropical Crop Science and Technology, 2021)
The study conducted at the Integrated Laboratory of the Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Malang, aimed to formulate granule and liquid biofertilizers for corn cultivation on dry land in Indonesia, covering 144.47 million hectares. Corn is a crucial agricultural commodity in the country, aligning with the Sustainable Food Self-Sufficiency Policy program. Fertilizers, especially biological ones with plant growth-promoting rhizobacteria (PGPR), play a pivotal role in enhancing both the quality and quantity of corn production. The research utilized a Nested Split Plot Design, considering varying levels of drought stress (100%, 70%, and 40% of field capacity) and bacterial density (control, 10^9, 10^8, and 10^7). Results indicated no significant interaction between granular and liquid fertilizer densities across different field capacities. While the PGPR consortium in both fertilizer types showed limited effectiveness in boosting maize growth and yield, the highest average performance was observed at a density of 10^7. Additionally, certain stress levels did not contribute to increased maize growth and yield, except for the 100% field capacity treatment. It was noted that extreme temperatures, reaching up to 54°C in the plastic house, might have hindered the expected interaction. Plant growth tends to decrease drastically below 15°C or above 40°C, as these temperatures activate physical and chemical processes in plants. The study underscores the importance of considering environmental factors in optimizing biofertilizer effectiveness for sustainable corn cultivation on Indonesian dry land.